Development and pilot of an online, personalized risk assessment tool for a breast cancer precision medicine trial - Holly Keane; Yash S. Huilgol; Yiwey Shieh; Jeffrey A. Tice; Jeff Belkora; Karen Sepucha; W. Patrick Shibley; Tianyi Wang; Mandy Che; Deborah Goodman; Elissa Ozanne; Allison Stover Fiscalini; et al. (npj Breast Cancer, 2021)
Abstract Breast cancer risk reduction has been validated by large-scale clinical trials, but uptake remains low. A risk communication tool could provide personalized risk-reduction information for high-risk women. A low-literacy-friendly, visual, and personalized tool was designed as part of the Women Informed to Screen Depending On Measures of risk (WISDOM) study. The tool integrates genetic, polygenic, and lifestyle factors, and quantifies the risk-reduction from undertaking medication and lifestyle interventions. The development and design process utilized feedback from clinicians, decision-making scientists, software engineers, and patient advocates. We piloted the tool with 17 study participants, collecting quantitative and qualitative feedback. Overall, participants felt they better understood their personalized breast cancer risk, were motivated to reduce their risk, and considered lifestyle interventions. The tool will be used to evaluate whether risk-based screening leads to more informed decisions and higher uptake of risk-reduction interventions among those most likely to benefit.